Design of a low voltage CMOS preamplifier - Wang, Bo (2010)
This report presents a “Fully Differential Folded-Cascode CMOS Operational Amplifier with class AB Push-pull Output Stages Design”. In order to design the most optimum operational amplifier which will be used as a preamplifier for audio/DVD applications, there are several important parameters to be considerate. The report contains all these parameters simulation results in details especially for the “flicker noise” or “1/f noise”. Since in CMOS operational amplifiers, the low frequency noise is usually dominated by flicker noise, therefore in preamplifier design to minimize noise becomes a most important design strategy in CMOS operational amplifiers. In this report several different types of operational amplifiers has been designed to compare their different performances. These operational amplifiers are “Two-stage CMOS Operational Amplifier”, “Folded-cascode CMOS Operational Amplifier”, “Fully Differential Folded-Cascode CMOS Operational Amplifier”, and “Fully Differential Folded-Cascode CMOS Operational Amplifier with class AB Push-pull Output Stages”. Report contains detail procedure of design, including theory, calculations, simulations, comparisons, conclusions and discussions.